2012
DOI: 10.1021/np300200j
|View full text |Cite
|
Sign up to set email alerts
|

Phomentrioloxin: A Phytotoxic Pentasubstituted Geranylcyclohexentriol Produced by Phomopsis sp., a Potential Mycoherbicide for Carthamus lanatus Biocontrol

Abstract: A new phytotoxic geranylcyclohexenetriol, named phomentrioloxin, was isolated from the liquid culture of Phomopsis sp., a fungal pathogen proposed for the biological control of Carthamus lanatus, a widespread and troublesome thistle weed belonging to the Asteraceae family causing severe crop and pastures losses in Australia. The structure of phomentrioloxin was established by spectroscopic, X-ray, and chemical methods as (1S,2S,3S,4S)-3-methoxy-6-(7-methyl-3-methylene-oct-6-en-1-ynyl)cyclohex-5-ene-1,2,4-triol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(91 citation statements)
references
References 35 publications
3
88
0
Order By: Relevance
“…84 Assayed on leaves of several weedy plants, i.e. 8, Table S1 ESI †), 86 was puried from the liquid culture of a Phomopsis sp. None of these compounds showed antibiotic, fungicidal or zootoxic activity.…”
Section: Aromatic Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…84 Assayed on leaves of several weedy plants, i.e. 8, Table S1 ESI †), 86 was puried from the liquid culture of a Phomopsis sp. None of these compounds showed antibiotic, fungicidal or zootoxic activity.…”
Section: Aromatic Compoundsmentioning
confidence: 99%
“…93 Poor results of mechanical 93 and chemical control have made this weed a suitable target for biological control. 86 A more virulent strain of D. gulyae was shown to produce different new and known metabolites when grown in a static liquid culture or in a bioreactor. 94 Tested at different concentrations against the host plants of C. lanatus L. and some other weeds (M. annua L., C. album L., C. arvense L., Sonchus oleraceus L. and S. viridis L.), phomentrioloxin (75) caused the appearance of necrotic spots when applied to the leaves of both the host and non host plants at 6.85 mM.…”
Section: Aromatic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strain of D . kongii used in this study was grown on a mineral defined liquid media, M1‐D as previously reported . The culture filtrates (7 L, pH 4.3), having high phytotoxic activity on leaves were lyophilized, dissolved in distilled water (1/10 of its original volume), and then extracted by EtOAc (4 x 700 mL).…”
Section: Methodsmentioning
confidence: 99%
“…gulyae was shown to produce phytotoxic metabolites when grown in vitro. The main metabolite, named phomentrioloxin, was characterized as (1 R , 2 R , 3 R , 4 R )‐3‐methoxy‐6‐(7‐methyl‐3‐methylene‐oct‐en‐1‐ynil)cyclohex‐5‐ene‐1,2,4‐triol …”
mentioning
confidence: 99%